2019
DOI: 10.1111/bcpt.13226
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐natal brain development as a target for urban air pollution

Abstract: Air pollution is the main urban‐related environmental hazard and one of the major contributors to the global burden of disease based on its cardiovascular‐respiratory impacts. In children, exposure to urban air pollution is associated, among others, with decelerated neurodevelopment early in life and increased risk of neurodevelopmental problems such as attention‐deficit hyperactivity disorder, autism spectrum disorders, academic failure and the start of Alzheimer's pathogenesis. However, the evidence of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 67 publications
2
38
0
1
Order By: Relevance
“…Placental expression of brain-derived neurotrophic factor (BDNF) and synapsin 1 (SYN1), two genes implicated in normal neurodevelopmental trajectories, decreased with increasing in utero exposure to PM 2.5 [68]. Direct or indirect maternal effects from air pollution, such as systemic low-grade inflammation, increased plasma viscosity, hormonal disruption or epigenetic changes, potentially impair placenta function and lead to neurological disruption by time of birth via mechanisms from decreased oxygen and nutrient transport [69].…”
Section: Supporting Evidence Of Prenatal Exposure To Trapmentioning
confidence: 99%
“…Placental expression of brain-derived neurotrophic factor (BDNF) and synapsin 1 (SYN1), two genes implicated in normal neurodevelopmental trajectories, decreased with increasing in utero exposure to PM 2.5 [68]. Direct or indirect maternal effects from air pollution, such as systemic low-grade inflammation, increased plasma viscosity, hormonal disruption or epigenetic changes, potentially impair placenta function and lead to neurological disruption by time of birth via mechanisms from decreased oxygen and nutrient transport [69].…”
Section: Supporting Evidence Of Prenatal Exposure To Trapmentioning
confidence: 99%
“…However, most of these studies are limited to developed countries (15,20). Recent evidence suggests that about 25 million children under 5 in LMICs are at risk of not reaching their full potential due to poverty, stunting, nutrient deficiency, violence, heavy metal exposure, and other social, biological, and physiological factors (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Such in utero exposure may not only influence fetal development and induce adverse pregnancy outcomes, but it can also adversely affect health in later life since the etiology of diseases in adulthood may have a fetal origin [ 2 ], as postulated in the Developmental Origins of Health and Disease hypothesis [ 3 ]. Various epidemiological studies identified associations between prenatal exposure to (ultra)fine particles and adverse health outcomes (i) at birth including an increased risk of low birth weight (< 2500 g) [ 4 , 5 ] and preterm birth (< 37 weeks of gestation) [ 6 , 7 ], and (ii) later in life such as cardiovascular disease [ 8 , 9 ], respiratory problems [ 10 , 11 ], and neurodevelopmental alterations [ 12 , 13 ]. (Ultra)fine particles refer to the particles that are incidentally generated and emitted in the (outdoor) air, often as by-products of fossil fuel combustion or industrial emission.…”
Section: Introductionmentioning
confidence: 99%